2019
DOI: 10.5897/ajb2019.16960
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 2-acetyl-1-pyrroline and aroma in Uganda rice populations with Oryza (barthi, glaberrima and sativa) backgrounds

Abstract: The sweet popcorn aroma conferred by 2-acetyl-1-pyrroline (2AP) is a highly economic trait of rice grain attracting premium price worldwide. This research study was conducted to determine the levels of 2AP in Ugandan rice lines with the aim of establishing a better understanding on the level and classes of 2AP and aroma phenotype. Concentration of 2AP was assayed using two-dimensional gas chromatography-time-of-flight mass spectrometry (GC × GC-TOF-MS) in tandem with sensory evaluation. Substantial variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…Sensory evaluation revealed that 23 accessions were aromatic (Table 4); while 33 accessions were non-aromatic, and further subdivided the accessions into three distinct groups of accessions depending on the strength of the aroma perceived by the panelist (Table 4). This result is in agreement with Ocan et al (2019) who also found differences in the strength of aroma among aromatic rice varieties. The strength of aroma is known to be influenced by cultivation condition such as temperature (Prodhan et al, 2017), Light intensity (Mo et al, 2015), plant nutrition (Lei et al, 2018) Figure 1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Sensory evaluation revealed that 23 accessions were aromatic (Table 4); while 33 accessions were non-aromatic, and further subdivided the accessions into three distinct groups of accessions depending on the strength of the aroma perceived by the panelist (Table 4). This result is in agreement with Ocan et al (2019) who also found differences in the strength of aroma among aromatic rice varieties. The strength of aroma is known to be influenced by cultivation condition such as temperature (Prodhan et al, 2017), Light intensity (Mo et al, 2015), plant nutrition (Lei et al, 2018) Figure 1.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, analysis of aroma in the grain using gas chromatography by measuring the amount of 2-Acetyl-1-Pyrroline (2AP), a compound that is responsible for aroma (Maravel et al, 2010;Daygon et al, 2017;Ocan et al, 2019). Finally, using DNA markers linked to aroma trait and Functional markers that target the polymorphism that define the functional and non-functional alleles of the aroma gene (Bradbury et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall mean abundance of VOCs, representative of previously established non-aromatic and aromatic rice lines (Ocan et al, 2019), were subjected to the Student's T-test at 5% significance level using Genstat software 18 th Ed. (VSN International, Hemel Hempstead, UK).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to Uganda, several rice germplasm were found to exhibit substantial variations in 2-AP abundance and most significantly, within similar aromatic categories (Ocan et al, 2019). The implication being that the substantial intra-group variations are most likely due to other VOCs, besides 2-AP, substantially contributing towards the rice aroma (Cho et al, 2013;Sansenya et al, 2018).…”
Section: Introductionmentioning
confidence: 98%